Estudio de la actividad citotóxica del compuesto Lurbinectedin sobre células leucocitarias normales y malignas de leucemia linfática crónica - De Los Ríos Alicandú, María Mercedes (2014)
Background: Lurbinectedin, an alkylating minor groove DNA-binder, has cytotoxic\nactivity against different solid tumors, but it has not been evaluated in hematological\nmalignancies yet. Chronic lymphocytic leukemia (CLL) is the most frequent leukemia in the adult and, despite the therapeutic advances made in recent years, it remains an\nincurable disease. The survival and proliferation of malignant B cells in CLL depend on\ntumor microenvironment signals which are given by non-malignant leukocytes, stromal\nand endothelial cells.\nObjectives: To investigate the cytotoxic activity of Lurbinectedin on human leukocyte\npopulations, comparing the sensitivity of B, T, NK cells and monocytes from healthy\ndonors and patients with CLL. To analyze the mechanism of cell death induced by\nLurbinectedin.\nMaterials and Methods: Isolation of human peripheral blood leukocytes and in vitro\nincubation with Lurbinectedin. Assessment of cell death with the fluorescent probe 7-\nAAD and flow cytometry analysis. Identification of leukocyte populations by specific\nantibodies. Detection of DNA breaks by evaluating ?H2AX expression by flow cytometry. Detection of PARP cleavage by Western blot.\nResults: Lurbinectedin induces cell death in a dose-dependent manner over all\nleukocyte populations evaluated, being normal and leukemic B cells and myeloid cells\nmore sensitive than T lymphocytes and NK cells. In samples from patients with CLL,\nLurbinectedin reduces viability of leukemic B cells through the elimination of nurse like\ncells differentiated from monocytes. The cytotoxic mechanism in CLL cells involves\nphosphorylation of histone H2AX and PARP fragmentation.\nConclusion: Lurbinectedin is an effective cytotoxic agent against leukemic B cells from\nCLL patients, inducing not only a direct but also an indirect effect by removing nurse\nlike cells that promote leukemic cells survival. Decreased sensitivity of T and NK cells to\nLurbinectedin would be an advantage for the treatment these patients who present a\ntypical immunosuppression.